PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT SUMBER BAROKAH DI LARANGAN TANGERANG - Nur Khasan Aprianto; Ading Sunarto (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of work motivation and work environment on employee performance at PT Sumber Barokah in Larangan Tangerang, both partially and simultaneously. The method used in this research is a quantitative method. Using survey techniques with the data collection instrument used, namely a questionnaire with a Likert scale. This research uses a sampling technique, namely a saturated sample with a total of 63 respondents. The data analysis used is instrument test, classical assumption test, multiple regression analysis, correlation coefficient test, determination test, and hypothesis test, namely t-count test and F-count test. The results of this research show that work motivation (X1) don’t has a positive and significant effect on employee performance. (Y), where the calculated t value < t table (1.342 < 2.002 and sig 0.005 < 0.05). And the work environment (X2) has a positive and significant effect on employee performance (Y) where the calculated t value > t table (4.691 > 2.002 and sig 0.00 < 0.05). So it can be stated that Work Motivation and Work Environment have a positive and significant influence on Employee Performance where the calculated f value > F table (136.263 > 3.15 and sig 0.000 < 0.05 or 0.000 < 0.005). this means that 82.0% of employee performance can be influenced by variables X1 (Work Motivation) and X2 (Work Environment) while the remaining 18.0% of employee performance is influenced by other variables not studied (such as work discipline and workers' wages)..